LO86: Improving time to analgesia administration for musculoskeletal injuries in the emergency department. (May 2019) - Woolner, V.; Ahluwalia, R.; Lum, H.; Beane, K.; De Leon, J.; Chartier, L.
Abstract : Background : Greater than 80% of patient visits to emergency departments (EDs) are for a pain-related concerns. Approximately 38, 000 patients per year have such complaints in our academic hospital ED. 3, 300 (8.6%) of those visits are for musculoskeletal (MSK) pain (i.e. back or extremity injury/pain), which are typically triaged as low-acuity presentations, leading to longer times to clinician assessment. Delays to adequate analgesia result in unnecessary suffering, worse patient care and satisfaction, and increased patient complaints.Aim Statement: We aimed to reduce the time-to-analgesia (TTA; time from patient triage to receipt of analgesia) for patients with MSK pain in our ED by 55% (to under 60 minutes) in 9 months' time (May 2018).Measures & Design : Our outcome measures were TTA (in minutes) and ED length of stay (LOS; in minutes). Process measures included nurses' use of medical directive and rate of analgesia administration. Balancing measures included patient adverse events and time spent triaging for nurses. We utilized weekly data capture for the Statistical Process Control (SPC) chart, and we used Mann-Whitney U test for our before-and-after evaluation. Utilizing the Model for Improvement, we performed wide stakeholder engagement and root cause analyses, and we created a Pareto chart. This led to our Plan-Do-Study-Act (PDSA) cycles: 1) nurse-initiated analgesia (NIA) at triage; 2) new triage documentation aid for medication administration; 3) quick reference medical directive badge tag for nurses; 4) weekly targeted feedback of the project's progress at clinical team huddle.Evaluation/Results: TTA decrease from 129 minutes (n = 153) to 100 minutes (22.5%; n = 87, p < 0.05). ED LOS decreased from 580 minutes (n = 361) to 519 minutes (10.5%; n = 187; p = 0.77). Special cause variation was identified on the ED LOS SPC chart with eight consecutive points below the midline, after PDSA 1. The number of patients who received any analgesia increased from 42% (n = 361) to 47% (n = 187; p = 0.13). The number of patients who received medications via medical directives increased from 22% (n = 150) to 44% (n = 87; p < 0.001). Balancing measures were unchanged.Discussion/Impact: The significant reduction in the TTA and increase in the use of medical directives in the before-and-after analyses were likely due to our front-line focused improvements and deliberate nursing engagement. With continued success and sustainable processes, we are planning to spread our project to other EDs and broaden our initiative to all pain-related concerns.